2015
DOI: 10.1159/000431152
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Signals the Onset of Depressive Behaviour in a Female Rat Model of Depression along with SSRI Treatment Resistance

Abstract: Depression is a serious condition that occurs more frequently in women and is often associated with treatment resistance. The main hypotheses of this study are that (a) aldosterone is an early marker of depression onset and (b) a tryptophan (TRP) depletion model of depression previously validated in male rats is treatment resistant in females. To explore possible underlying mechanisms, we have focused on factors shown to be altered in patients with treatment-resistant depression. Female Sprague-Dawley rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
2
14
1
Order By: Relevance
“…Almost all known antidepressant drugs stimulate 5-HT transmission, either directly or indirectly (Dremencov, 2009; Pavlovicova et al, 2015). Accordingly, tryptophan depletion and the subsequent decrease in 5-HT bioavailability leads to the onset of the symptoms of depression (Delgado et al, 1994, 1999; Franklin et al, 2015). Since increased excitability of 5-HT neurons leads to the increased synaptic levels of 5-HT in the brain, it is possible that the anxiolytic and antidepressant effect of physical exercise, reported in previous studies in animal models (Greenwood et al, 2003; Lapmanee et al, 2012; Chen et al, 2016) and human subjects (Kvam et al, 2016) is mediated, at least in part, via increased excitability of 5-HT neurons in the DRN.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all known antidepressant drugs stimulate 5-HT transmission, either directly or indirectly (Dremencov, 2009; Pavlovicova et al, 2015). Accordingly, tryptophan depletion and the subsequent decrease in 5-HT bioavailability leads to the onset of the symptoms of depression (Delgado et al, 1994, 1999; Franklin et al, 2015). Since increased excitability of 5-HT neurons leads to the increased synaptic levels of 5-HT in the brain, it is possible that the anxiolytic and antidepressant effect of physical exercise, reported in previous studies in animal models (Greenwood et al, 2003; Lapmanee et al, 2012; Chen et al, 2016) and human subjects (Kvam et al, 2016) is mediated, at least in part, via increased excitability of 5-HT neurons in the DRN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, childhood adversity is associated with altered cortisol and DHEA secretion 55 , which in turn increases the risk of depression 65,66 . Furthermore, aldosterone induces depressive symptoms in animals 64,67 . On the other hand, depression itself can alter steroid hormone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that aldosterone secretion had increased already after 4 days of tryptophan depletion, prior to the rise in serum corticosterone. This finding suggests that aldosterone may be more important than corticosterone in the development of a depression-like state and aldosterone may constitute an early marker for the onset of depression-like behavior [30].…”
Section: Nothing Dared Nothing Wonmentioning
confidence: 91%
“…We have established a new and novel animal model of depression based on diet-induced tryptophan depletion in female rats [29]. Diet-induced tryptophan depletion resulted in a significant reduction of brain serotonin and induction of depressionlike behavior manifested by increased immobility in the forced swim test [30]. Interestingly, the depression-like state was associated with a significant increase in serum aldosterone concentrations.…”
Section: Nothing Dared Nothing Wonmentioning
confidence: 99%